2020
DOI: 10.3390/polym12040923
|View full text |Cite
|
Sign up to set email alerts
|

Electrically-Conductive Polyketone Nanocomposites Based on Reduced Graphene Oxide

Abstract: In this work, we investigated the functionalization of polyketone 30 (PK30) with glycyl-glycine (Gly-Gly) via the Paal–Knorr reaction with the aim of homogenously dispersing two types of reduced graphene oxide (rGO, i.e., lrGO and hrGO, the former characterized by a lower degree of reduction in comparison to the latter) by non-covalent interactions. The functional PK30-Gly-Gly polymer was effective in preparing composites with homogeneously distributed rGO characterized by an effective percolation threshold at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 60 publications
(72 reference statements)
0
15
0
Order By: Relevance
“…It has been demonstrated that PMMA-based BCs cannot form covalent bonds with the natural bone, and a lack of interactions may induce implant loosening after a while. According to the results, the addition of CNTs, GO, and carbon-based composites [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 ] can enhance the setting times, temperature, strength, bioactivity, and cellular activity of the PMMA-based BCs. However, it is believed that utilization of GO could have further impact than CNTs reinforcing agents on enhancement of the strength and durability of PMMA-based BCs, conquering the potential issue presented by premature failure of the implant.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that PMMA-based BCs cannot form covalent bonds with the natural bone, and a lack of interactions may induce implant loosening after a while. According to the results, the addition of CNTs, GO, and carbon-based composites [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 ] can enhance the setting times, temperature, strength, bioactivity, and cellular activity of the PMMA-based BCs. However, it is believed that utilization of GO could have further impact than CNTs reinforcing agents on enhancement of the strength and durability of PMMA-based BCs, conquering the potential issue presented by premature failure of the implant.…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic morphology of the composite samples was observed by scanning electron microscopy (SEM) using a Dual Beam FIB/SEM Helios Nano-Lab 600i (FEI, Hillsboro, OR, USA) in a way similar to procedures previously reported [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The temperature was monitored with a k-thermocouple brought in contact with the sample; the resistance was continuously measured using a High precision multimeter (Model 187, Fluke, Fluke Corporation, Everett, WA, USA) connected with the copper electrodes. Measurements were performed modulating the temperature by changing the current applied to the ceramic heater and waiting for the temperature stabilization [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pucci et al investigated the functionalization of polyketone 30 (PK30) with glycyl-glycine (Gly-Gly) via the Paal-Knorr reaction with the aim of homogenously dispersing two types of reduced graphene oxide (rGO, i.e., lrGO and hrGO, the former characterized by a lower degree of reduction in comparison to the latter) by non-covalent interactions. All the composites showed a typical semiconductive behavior and stable electrical response after several heating/cooling cycles from 30 to 115 • C, demonstrating their usability as an ON-OFF temperature sensor and as sensing material in soft robotics applications [6].…”
mentioning
confidence: 90%